Doing without believing – enacting policy in the English primary school. Issue 4 (7th August 2020) - Braun, Annette; Maguire, Meg
ABSTRACT: This paper explores how six English primary school teachers enact assessment and attainment-focused policy and asks what this performative policy work does and whether it shapes or requires a new kind of primary teacher subjectivity. The paper draws on a small study of policy enactments in two primary schools in Greater London in order to discuss two dimensions of policy enactment that emerged from our data: first, shifting assessment regimes in primary schools which create an enactment environment of second-guessing policy; second, a shift in focus from the individual child to targeted groups that raises questions about more traditional primary school values. The paper concludes with a reflection on the effects of contradictory values and practices and how this policy context creates a form of 'doing without believing' in the English primary school.